PENGARUH MARKET PLACE DALAM MEMODERASI GAYA HIDUP DAN HARGA TERHADAP KEPUTUSAN MEMBELI DI PASAR KONVENSIONAL: (Studi Kasus Perubahan Keputusan Pembelian Konsumen) - Triana Anggraini; Devit Setiono; Taqwa Putra Budi Purnomo Sidi Hiram (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
The research aims to find out whether market place moderate lifestyle and price on purchasing decisions in conventional markets. The sample used was 88 respondents, obtained using google from in 2023. Analysis used smart PLS with outer and inner model. The results obtained show that lifestyle and price influence purchasing decisions in conventional markets, market place moderates the relationship between lifestyle and purchasing decisions in conventional markets and market place cannot moderate the relationship between price and purchasing decisions in conventional markets.